(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The southern regions of Uzbekistan, including the Kashkadarya and Surkhandarya regions, as well as the adjacent mountain ranges, have significant potential for the development of mineral deposits. Effective development of these rich resources requires the introduction of advanced innovative technologies at all stages of the mining process - from the stage of development (extraction) to mineral processing. This paper examines modern approaches and technological solutions aimed at increasing productivity, reducing the environmental burden and improving the economic efficiency of mining enterprises in the region, which will significantly improve the use of available natural resources and minimize negative impacts on the environment